PENGEMBANGAN MEDIA KARTUN FISIKA PADA MATA PELAJARAN FISIKA KELAS VII MATERI GERAK - Masmin, Masmin; Haris, Venny; Mahrizal, Mahrizal (Jurnal Pembelajaran MIPA, 2014)
The aim of this research was to crate physic cartoon media which valid and pratical that can help the seventh grade students to understand the movement. This is a research and development with 4-D research design. The research procedures divide into three steps, namely defining, designing, and developing. The research instrument that used is validation sheets, observation sheets and response questionnaire sheets. The research instrument is developed by arranging the item instrument, doing the validity test, and doing try out and analyzing the practical result. The finding of the research showed that 1). The physic cartoon about movement is valid with percentage 81,16% (consist of content validity and construct validity) from physics education expertâs aspect. 2) The use of physics cartoon media about movement in learning process did not have problem, in practical meaning, it use depend on observerâs and studentsâ evaluation.Key words: Development, cartoon media, physics subject, movement.